A Compendium of Chronic Obstructive Pulmonary Disease - Chung Ong, Kian (IntechOpen, 2023)
The commonness and complexity of COPD necessitate rapid communication of significant new knowledge of the disease. This book provides a platform for sharing new notions in scientific research as well as contemporary clinical best practices. It combines noetic theoretical concepts with the ontic practical management of COPD. Epistemological concepts explored in this book include contextualization in the evaluation and treatment of COPD, as well as the latest in the basic science of airway inflammation, "omics" research, and delivery therapeutics. Practical topics addressed include early detection and alleviation of COPD exacerbation, pulmonary rehabilitation, and identifying phenotypes or treatable traits to optimize inhaled therapy.